Enhancing Tourism Destination Services and Promotion Through IT-Based Management - Budiningtyas, R.R. Erna Sadiarti; Zega, Imanuel; Dangga, Sebastianus; Rizal, Moch. Deni; Jayanawi, Briggitta Hernya Only (Research Horizon, 2025)
Baluwarti Village, Surakarta, is a cultural heritage area with tourism potential that has not been optimized due to manual marketing and lack of financial literacy. This community service activity aims to improve the quality of services, marketing, and income of micro, small, and medium enterprises through information technology and training. The methods used include training on local potential, break-even point calculation, website management, and mentoring for the Teman Solo Community. The results showed 85 percent of participants understood the tourism potential of Baluwarti, the selling price of micro, small, and medium enterprises' products decreased by 15 percent after the break-even point training, and the Baluwarti Experience website processed 50 online bookings in two months. Tourist visits increased from 30 to 70 people per month, with micro, small, and medium enterprises' income increasing by 22 percent. Tourist satisfaction also increased from a score of 3.8 to 4.3 on a scale of 5. This activity successfully empowered the community through digitization and financial literacy, supported the sustainability of culture-based tourism, and can be replicated in other destinations.